2(x+3)(x-4)=2(x-3)

Simple and best practice solution for 2(x+3)(x-4)=2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+3)(x-4)=2(x-3) equation:


Simplifying
2(x + 3)(x + -4) = 2(x + -3)

Reorder the terms:
2(3 + x)(x + -4) = 2(x + -3)

Reorder the terms:
2(3 + x)(-4 + x) = 2(x + -3)

Multiply (3 + x) * (-4 + x)
2(3(-4 + x) + x(-4 + x)) = 2(x + -3)
2((-4 * 3 + x * 3) + x(-4 + x)) = 2(x + -3)
2((-12 + 3x) + x(-4 + x)) = 2(x + -3)
2(-12 + 3x + (-4 * x + x * x)) = 2(x + -3)
2(-12 + 3x + (-4x + x2)) = 2(x + -3)

Combine like terms: 3x + -4x = -1x
2(-12 + -1x + x2) = 2(x + -3)
(-12 * 2 + -1x * 2 + x2 * 2) = 2(x + -3)
(-24 + -2x + 2x2) = 2(x + -3)

Reorder the terms:
-24 + -2x + 2x2 = 2(-3 + x)
-24 + -2x + 2x2 = (-3 * 2 + x * 2)
-24 + -2x + 2x2 = (-6 + 2x)

Solving
-24 + -2x + 2x2 = -6 + 2x

Solving for variable 'x'.

Reorder the terms:
-24 + 6 + -2x + -2x + 2x2 = -6 + 2x + 6 + -2x

Combine like terms: -24 + 6 = -18
-18 + -2x + -2x + 2x2 = -6 + 2x + 6 + -2x

Combine like terms: -2x + -2x = -4x
-18 + -4x + 2x2 = -6 + 2x + 6 + -2x

Reorder the terms:
-18 + -4x + 2x2 = -6 + 6 + 2x + -2x

Combine like terms: -6 + 6 = 0
-18 + -4x + 2x2 = 0 + 2x + -2x
-18 + -4x + 2x2 = 2x + -2x

Combine like terms: 2x + -2x = 0
-18 + -4x + 2x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-9 + -2x + x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-9 + -2x + x2)' equal to zero and attempt to solve: Simplifying -9 + -2x + x2 = 0 Solving -9 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '9' to each side of the equation. -9 + -2x + 9 + x2 = 0 + 9 Reorder the terms: -9 + 9 + -2x + x2 = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -2x + x2 = 0 + 9 -2x + x2 = 0 + 9 Combine like terms: 0 + 9 = 9 -2x + x2 = 9 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 9 + 1 Reorder the terms: 1 + -2x + x2 = 9 + 1 Combine like terms: 9 + 1 = 10 1 + -2x + x2 = 10 Factor a perfect square on the left side: (x + -1)(x + -1) = 10 Calculate the square root of the right side: 3.16227766 Break this problem into two subproblems by setting (x + -1) equal to 3.16227766 and -3.16227766.

Subproblem 1

x + -1 = 3.16227766 Simplifying x + -1 = 3.16227766 Reorder the terms: -1 + x = 3.16227766 Solving -1 + x = 3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 3.16227766 + 1 Combine like terms: -1 + 1 = 0 0 + x = 3.16227766 + 1 x = 3.16227766 + 1 Combine like terms: 3.16227766 + 1 = 4.16227766 x = 4.16227766 Simplifying x = 4.16227766

Subproblem 2

x + -1 = -3.16227766 Simplifying x + -1 = -3.16227766 Reorder the terms: -1 + x = -3.16227766 Solving -1 + x = -3.16227766 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -3.16227766 + 1 Combine like terms: -1 + 1 = 0 0 + x = -3.16227766 + 1 x = -3.16227766 + 1 Combine like terms: -3.16227766 + 1 = -2.16227766 x = -2.16227766 Simplifying x = -2.16227766

Solution

The solution to the problem is based on the solutions from the subproblems. x = {4.16227766, -2.16227766}

Solution

x = {4.16227766, -2.16227766}

See similar equations:

| -512=16a | | (r+1)/3=8 | | r+1/3=8 | | 14m=392 | | (x-8)+12=100 | | 3-(4+r)=7 | | 28-k=35 | | (y-8)-(y+3)=7y | | 3X+13+12=14 | | c+0.7=2.3 | | 4(x-9)=16x | | 0.5=0.5i-2 | | 12+3x+13=14 | | -5.1+a=-6.6 | | 28=y+14 | | 26x+14=5(5x+5) | | w-83=-100 | | 0=19+t | | 2X+1=3X-11 | | 7+2X+1=3X-11 | | y+80=-45 | | n-24=-16 | | -54+m=82 | | 30x^2-44x+16=0 | | y+8=21 | | a-9=13 | | 4x-3(x-2)=16 | | 250+14h=22h | | 3=5x+12 | | t+(2t+4)=-5 | | 8x/3-5x/4=-13 | | 5/25=y/85 |

Equations solver categories